W stronę badań słowiańskich kontekstów staropolskich apokryfów (1) O czeskiej podstawie fragmentu Rozmyślania przemyskiego - Borowiec, Karolina (Slavia Occidentalis, 2015)
The goal of this article is to provide evidence that the author of Rozmyślanie przemyskie resorted to non-Latin written sources when writing his apocrypha. The author of this article has analysed the parts of the oldest Czech version of Život Krista Pána and the analogical parts of Rozmyślanie przemyskie and has indicated the similarities and records which undoubtedly result from an erroneous interpretation or the translator’s wrong understanding of the sense of the Czech version. Therefore evidence has been provided that the Polish version of the apocrypha was based also on the Czech source. By excluding a possibility of the author resorting directly to the full version of the Czech apocrypha (rather, he included into the narration a Czech sermon or a piece of Život Krista Pána which existed as a separate text), the author of the article suggests that the Polish Biblical apocrypha be viewed with respect to the Czech texts.